Relationship Between Dams, Knickpoints and the Longitudinal Profile of the Upper Indus River - Zhou, Liqin; Liu, Weiming; Chen, Xiaoqing; Wang, Hao; Hu, Xudong; Li, Xuemei; Schwanghart, Wolfgang (Frontiers in Earth Science, 2021)
Mass movements in mountainous areas are capable of damming rivers and can have a lasting effect on the river longitudinal profile. The long profile is commonly used to retrieve regional tectonic information, but how much dams may compromise geomorphometry-based tectonic analysis has not been systematically researched. In this study, we investigate the relationship between river dams and the longitudinal profile of the upper Indus River basin, based on interpretation and analysis of remote sensing imagery and digital elevation models (DEMs) and local field work. We identified 178 landslide, glacier and debris flow dams. Using TopoToolbox, we automatically extracted the river longitudinal profile from the 30 m SRTM DEM, determined the location of convex knickpoints and calculated the channel steepness index. One hundred and two knickpoints were detected with heights above 148 m, of which 55 were related to dams. There is good spatial correspondence between dams, convexities in the river longitudinal profile and relatively high steepness index. Different dam types have different impacts on the river profile; on the upper Indus, debris flow dams have a greater impact than landslide and glacier dams and can form knickpoints of up to 900 m. Therefore, dams may have a significant influence on the river longitudinal profile, knickpoints and steepness index, and should be considered when extracting information on regional tectonics using these indices.